The Level of Happiness Among Counselling Students in Malaysia - Eng, Su Yin; Guan, Teik Ee (Southeast Asia Psychology Journal, 2022)
This study examined the level of happiness among counselling students in seven public universities in Malaysia (N = 299). On the rage, the counselling students' happiness score was 3.49 (SD = 0.502). This is a moderate score for happiness. The positive items most strongly agreed by participants were item 3 “I feel that life is very useful,” endorsed by 22.4% of the participants, followed by item 9 “Life is good” by 21.7% and em 11 “I always laugh by 15.7% of the participants. On the other hand, the negative items strongly disagreed by participants were item 29 “I have no happy memories of the past,” endorsed by 52.5% of the participants, followed by item 24 “I have no particular meaning and purpose in my life,” endorsed by 43.5 of the participants and item 10 “I don't think that the world is a good place” endorsed by 42.5% of the participants. This showed that even though the level of happiness was only moderate, students still thought that life was good and meaningful. As for the difference of happiness between genders, the result showed that there was no significant difference of happiness between genders t (297)= 1.88, p>.05. This could be due to the equal opportunities given to all students; thus males and females shoulders the same responsibilities and burdens. The students went through the same Movement Control Orders and therefore had the same experiences in this hard time.